Dynamic parameter estimation problem for ethanol production from seaweed - Delpino, Claudio (2014)
Ethanol has been studied extensively as one of the current and probably future energy vectors. Fermentation of hydrolysed oligosaccharides from macroalgae biomass to ethanol has been certified, and several processing options have been proposed. In the present work, we model the production of ethanol based on Laminaria, a seaweed genus that belongs to the so-called "brown algae" group, as the carbon source. In brown algae, the most relevant sugars that can be used as substrate for fermentation are mannitol -the alcohol form of the sugar mannose- and laminaran, a linear polysaccharide of(1,3)-β-Dglucopyranose. We consider the yeast Pichia angophorae as the fermenting microorganism. The model includes dynamic mass balances for biomass, ethanol, mannitol and laminaran. Growth is controlled via limiting functions that modify the biomass equation for temperature and oxygen transfer rate (OTR). It is also modified by including a term that considers inhibition by ethanol. Based on the proposed model, a dynamic parameter estimation problem is formulated, the objective function being weighted least-squares fit to data, subject to the mass balance equations. The data set for parameter estimation was obtained in batch liquid cultures, with experiments performed over 40 hours. Numerical results provide useful insights on ethanol production using macroalgae biomass as carbon source